Critical Nursing Care With Nursing Problems, Impaired Gas Exchange and Inhibition of Spontaneous Ventilation in Patient with Coronary Heart Disease: A Case Study - Suwardianto, Heru (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Coronary heart disease is the highest cause of death and requires nursing care that is quite complex to overcome. The purpose of this study was to determine the description of nursing care on gas exchange disorders, nursing problems, and inhibition of spontaneous ventilation in patients with coronary heart disease. The research method uses a case study. The study population was critical patients with a medical diagnosis of coronary heart disease who were admitted to the ICU. The study sample was critical patients with nursing problems, impaired gas exchange, and inhibition of spontaneous ventilation. The research variables were assessment, nursing diagnosis, intervention, implementation, and evaluation. The instrument used was the critical nursing care format.